Land, Politics, and Memory in Five Nija'ib' K'iche' Títulos : "The Title and Proof of Our Ancestors" - Matsumoto, Mallory (Book collections on Project MUSE., 2017)
Land, Politics, and Memory in Five Nija'ib' K'iche' Títulos is a careful analysis and translation of five Highland Maya títulos composed in the sixteenth century by the Nija'ib' K'iche' of Guatemala. The Spanish conquest of Highland Guatemala entailed a series of sweeping changes to indigenous society, not the least of which were the introduction of the Roman alphabet and the imposition of a European system of colonial government. Introducing the history of these documents and placing them within the context of colonial-era Guatemala, this volume provides valuable information concerning colonial period orthographic practice, the K'iche' language, and language contact in Highland Guatemala. For each text, author Mallory E. Matsumoto provides a photographic copy of the original document, a transliteration of its sixteenth-century modified Latin script, a transcription into modern orthography, an extensive morphologic analysis, and a line-by-line translation into English, as well as separate prose versions of the transcription and translation. No complete English translation of this set of manuscripts has been available before, nor has any Highland Maya título previously received such extensive analytical treatment. Offering insight into the reality of indigenous Highland communities during this period, Land, Politics, and Memory in Five Nija'ib' K'iche' Títulos is an important primary source for linguists, historians, and experts in comparative literature. It will also be of significant interest to students and scholars of ethnohistory, linguistics, Latin American studies, anthropology, and archaeology.